Tibia Tubercle Distalization Osteotomy: A Surgical Technique. Issue 1 (March 2022) - DiBartola, Alex C.; Magnussen, Robert A.; Perez, Althea A.; Fitzpatrick, Sean; Smith, Scott; Flanigan, David C.
Abstract : Patella alta increases the risk of recurrent patellar instability. The complex movement of the patellofemoral joint may be altered in a growing number of ways to address various conditions that contribute to patellar instability. We describe a tibial tubercle distalization procedure for the management of patella alta in the setting of recurrent patellar instability.